2019
DOI: 10.1021/acsami.9b19798
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a High Average zT Value in Sb2Te3-Based Segmented Thermoelectric Materials

Abstract: A tiny amount of Mn is doped in In0.15Sb1.85Te3 sample to tailor its carrier concentration, thus boosting the power factor and suppressing the bipolar effect. Furthermore, large amounts of nanotwins are constructed to effectively scatter the phonons and reduce the lattice thermal conductivity. As a result, the zT value of Mn0.02In0.15Sb1.83Te3 is enhanced up to 1.0 at 673 K, making this material a robust candidate for medium-temperature (500–673 K) thermoelectric applications. Then combining with the low-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…At 373 K, the maximum ZT of BTS + 1.5 wt % Y 2 O 3 NC reaches 1.21, which is much higher than that of the pristine BTS (0.67). It should be noted that the ZT values of the BTS composite with 1.5 wt % Y 2 O 3 keep above unity over the entire operative temperature range, which is superior to most of the n-type Bi 2 Te 3 -based thermoelectric materials in recent years. , The value of ZT ave can be obtained by integrating the area under ZT curves according to the formula: …”
Section: Results and Discussionmentioning
confidence: 99%
“…At 373 K, the maximum ZT of BTS + 1.5 wt % Y 2 O 3 NC reaches 1.21, which is much higher than that of the pristine BTS (0.67). It should be noted that the ZT values of the BTS composite with 1.5 wt % Y 2 O 3 keep above unity over the entire operative temperature range, which is superior to most of the n-type Bi 2 Te 3 -based thermoelectric materials in recent years. , The value of ZT ave can be obtained by integrating the area under ZT curves according to the formula: …”
Section: Results and Discussionmentioning
confidence: 99%
“…Compared to the pristine Bi 0.4 Sb 1.6 Te 3 , the S of MgB 2 doped samples is drastically decreased. Based on the assumption of the single parabolic band (SPB) model, [ 14 ] the Pisarenko curve is calculated and plotted in Figure S1, Supporting Information. All experimental results match well with the calculated line, indicating that MgB 2 doping has almost no influence on the valence band structure.…”
Section: Resultsmentioning
confidence: 99%
“…[35] In the past decade, nanotwins have been reported in these Bi 2 Te 3 based alloys prepared by ball milling followed by hot pressing. [36][37][38][39][40] Besides, Hayashi et al also reported the occur-rence of twins in the Bi 1.9 Sb 0.1 Te 2.7 Se 0.3 prepared by equal channel angular extrusion. [41] In these works, the twins are thought to be generated from the severe deformation, similar to the deforming twins observed in face-centered cubic (FCC) crystals with nanocrystal grains.…”
Section: Introductionmentioning
confidence: 99%
“…[ 35 ] In the past decade, nanotwins have been reported in these Bi 2 Te 3 based alloys prepared by ball milling followed by hot pressing. [ 36–40 ] Besides, Hayashi et al. also reported the occurrence of twins in the Bi 1.9 Sb 0.1 Te 2.7 Se 0.3 prepared by equal channel angular extrusion.…”
Section: Introductionmentioning
confidence: 99%